2017
DOI: 10.3390/agronomy7030058
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Semiochemical Mediated Plant Defense in Cereals: A Novel Strategy for Crop Protection

Abstract: Plants have evolved highly intriguing ways of defending themselves against insect attacks, including through emission of defense volatiles. These volatiles serve the plant's defense by directly repelling phytophagous insects and/or indirectly through attracting natural enemies antagonistic to the herbivores. Several laboratory studies established the potential of improving plant resistance against insect attacks by manipulating the plant-derived volatile semiochemicals emissions. Yet, more efforts need to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Because it was found that volatiles have an important role in host localization and the parasitic and predation behavior of parasitoids to pests, 58,59 these volatiles are regarded as potential tools with which to enhance the recruitment of parasitoids for biological control. 60 Importantly, the blend of plant volatiles has an important role in biological control, and provides more information for parasitoids than the individual components in a tritrophic system. 61 The effectiveness of using volatile mixtures rather than single compounds has been tested in field and laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Because it was found that volatiles have an important role in host localization and the parasitic and predation behavior of parasitoids to pests, 58,59 these volatiles are regarded as potential tools with which to enhance the recruitment of parasitoids for biological control. 60 Importantly, the blend of plant volatiles has an important role in biological control, and provides more information for parasitoids than the individual components in a tritrophic system. 61 The effectiveness of using volatile mixtures rather than single compounds has been tested in field and laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Plant-derived volatile semiochemicals can be exploited to manipulate insect pest behaviour in an integrated pest management strategy. 9 Previous studies demonstrated the attractiveness of plant volatiles to different noctuid moths. For example, volatile compounds released from pigeon pea (Cajanus cajan) and chickpea (Cicer arietinum) were shown to be attractive to Helicoverpa armigera moths in the laboratory and field.…”
Section: Introductionmentioning
confidence: 99%
“…Plant‐derived volatile semiochemicals can be exploited to manipulate insect pest behaviour in an integrated pest management strategy 9 . Previous studies demonstrated the attractiveness of plant volatiles to different noctuid moths.…”
Section: Introductionmentioning
confidence: 99%
“…Diorhabda tarsalis can locate G. uralensis by responding to the volatile chemicals released from the plant. Conversely, many plants release defensive substances after insect damage (Tamiru and Khan, 2017) that directly repel pests or attract the pest's natural enemies (Lucchi et al, 2017;Salamanca et al, 2019;Rim et al, 2020). For example, 4-oxo-(E)-2-hexenal emitted from Tamarix spp.…”
Section: Discussionmentioning
confidence: 99%